Analisis Peran Microteaching dalam Mengembangkan Keterampilan Dasar Mengajar Calon Guru PAI - Suparmita S; Shella Andana; Sulis Dian Ningsih; Siti Darojatun Anisak (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the role of microteaching in developing the basic teaching skills of prospective Islamic Religious Education (PAI) teachers. Microteaching is a teaching training method designed to help prospective Islamic Religious Education (PAI) teacher candidates practice their teaching skills in a gradual, systematic, and focused manner. This study employed qualitative methods with a descriptive approach. Data collection techniques included observation, interviews, and documentation of prospective Islamic Religious Education (PAI) teacher candidates participating in microteaching activities. The results indicate that microteaching plays a significant role in improving basic teaching skills, such as opening and closing lessons, explaining material, asking questions, managing the classroom, using learning media, and establishing effective communication with students. Furthermore, microteaching also helps students increase their self-confidence, critical thinking skills, and readiness for direct teaching practice in schools. Thus, microteaching is an effective tool for optimally and professionally developing the pedagogical competence of prospective Islamic Religious Education (PAI) teachers.